SPSS Trends 6.1 (SPSS, 1994)
SPSS Trends is a forecasting and time series tool with multiple curve fitting models, smoothing models and methods for estimating autoregressive functions. The Trends option enables you to use powerful ARIMA modeling techniques, including XIIARIMA, and four other state-of-the-art estimation procedures.
Keywords: SPSS 6.1; lékařská informatika